2017
DOI: 10.1080/16546628.2017.1321347
|View full text |Cite
|
Sign up to set email alerts
|

Acute selective bioactivity of grape seed proanthocyanidins on enteroendocrine secretions in the gastrointestinal tract

Abstract: Background: Enteroendocrine cells respond to food components by secreting an array of hormones that regulate several functions. We have previously shown that grape seed proanthocyanidins (GSPE) modulate GLP-1 levels.Objective: To deepen on the knowledge of the mechanisms used by GSPE to increase GLP-1, and extend it to its role at modulation of other enterohormones.Design: We used an ex vivo system to test direct modulation of enterohormones; STC-1 cells to test pure phenolic compounds; and rats to test the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
27
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 40 publications
(55 reference statements)
5
27
1
Order By: Relevance
“…We had previously shown that gallic acid reduced CCK secretion after an acute treatment in a rat duodenum ex vivo model. 9 Now we found that CCK plasma levels tended to increase after an 8-day treatment with gallic acid. These differences might be due to the different length of time of each treatment (acute vs. 8 days).…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…We had previously shown that gallic acid reduced CCK secretion after an acute treatment in a rat duodenum ex vivo model. 9 Now we found that CCK plasma levels tended to increase after an 8-day treatment with gallic acid. These differences might be due to the different length of time of each treatment (acute vs. 8 days).…”
Section: Discussionmentioning
confidence: 71%
“…5 However, other effects might be mediated through interactions with the gastrointestinal tract where they act by inhibiting enzymes, 6 modulating inflammation and/or gut barrier properties, 7 or modulating enteroendocrine secretion. 8,9 The effects of flavonoids on gut microbiota have been recently reviewed; 7 but there are few studies analyzing the role of proanthocyanidins on gut microbiota which could also mediate their physiological effects.…”
Section: Introductionmentioning
confidence: 99%
“…The authors showed that GSPE treatment increased GLP-1 levels in the ileum, while the unabsorbed GSPE's and phenolic microbial metabolites did so in the colon. These findings suggest that unabsorbed polyphenols with high degree of polymerization and microbiota-metabolized phenolic compounds act on enteroendocrine L-cells to promote GLP-1 secretion 27 . Further studies will be needed to determine whether the protection from glucose intolerance that are linked to unabsorbed polymeric PACs from blueberry can be linked to other intestinal targets that are linked to pancreatic beta-cell insulin secretion or hepatic insulin clearance.…”
Section: Discussionmentioning
confidence: 85%
“…In this regard, proanthocyanidins have been shown to mimic insulin effects by affecting intestinal glucose transporters 26 and stimulating intestinal hormones which are involved in the modulation of digestion and metabolism 27 . For instance, Casanova-Martí et al 27 demonstrated, both in vivo and ex vivo, the role of grape seed proanthocyanidins (GSPE) on the induction of enterohormones secretion in different parts of the intestine, leading to glucose homeostasis regulation. The authors showed that GSPE treatment increased GLP-1 levels in the ileum, while the unabsorbed GSPE's and phenolic microbial metabolites did so in the colon.…”
Section: Discussionmentioning
confidence: 99%
“…Acute GSPE treatment inhibits intestinal gluconeogenesis, downregulates the expression of the glucose transporter Glut-2 and glucokinase in the liver and pancreas [91], reduces the uptake of glucose in the liver and pancreas, resulting in increased levels of portal vein glucose. During fasting, the portal vein glucose level maintained satiety to a certain extent [92]. When glucose is present in the intestine, it stimulates the secretion of intestinal hormones related to satiety in the colon, such as glucagon-like peptide (GLP-1), peptide YY, cholecystokinin and ghrelin.…”
Section: Reduce Food Intakementioning
confidence: 99%